Terahertz Probing Irreversible Phase Transitions Related to Polar Clusters in Bi0.5Na0.5TiO3‐Based Ferroelectric - Jiyue Wu; Wenfeng Sun; Nan Meng; Hangfeng Zhang; Vladimir Koval; Yan Zhang; Robert Donnan; Bin Yang; Dou Zhang; Haixue Yan (Advanced Electronic Materials, 2020)
Abstract Electric‐field‐induced phase transitions in Bi0.5Na0.5TiO3‐based relaxor ferroelectrics are essential to the control of their electrical properties and consequently in revolutionizing their dielectric and piezoelectric applications. However, fundamental understanding of these transitions is a long‐standing challenge due to their complex crystal structures. Given the structural inhomogeneity at the nanoscale or sub‐nanoscale in these materials, dielectric response characterization based on terahertz (THz) electromagnetic‐probe beam fields is intrinsically coordinated to lattice dynamics during DC‐biased poling cycles. The complex permittivity reveals the field‐induced phase transitions to be irreversible. This profoundly counters the claim of reversibility, the conventional support for which is based upon the peak that is manifest in each of four quadrants of the current–field curves. The mechanism of this irreversibility is solely attributed to polar clusters in the transformed lattices. These represent an extrinsic factor, which is quiescent in the THz spectral domain.